Effects of the MDM2 inhibitor Nutlin-3a on sensitivity of pancreatic cancer cells to berberine and modified berberines in the presence and absence of WT-TP53. (January 2022) - Abrams, Stephen L.; Akula, Shaw M.; Steelman, Linda S.; Follo, Matilde L.; Cocco, Lucio; Ratti, Stefano; Martelli, Alberto M.; Libra, Massimo; Falzone, Luca; Candido, Saverio; Montalto, Giuseppe; Cervello, Melchiorre; et al.
Abstract: Approaches to improve pancreatic cancer therapy are essential as this disease has a very bleak outcome. Approximately 80% of pancreatic cancers are pancreatic ductal adenocarcinomas (PDAC). A key regulatory gene frequently mutated (∼75%) in PDAC is the TP53 tumor suppressor gene which controls the transcription of multiple genes involved in cell cycle progression, apoptosis, cancer progression and other growth regulatory processes. The mouse double minute 2 homolog (MDM2) gene product is a nuclear-localized E3 ubiquitin ligase and negatively regulates the TP53 protein which results in its proteasomal degradation. Various MDM2 inhibitors have been isolated and examined in clinical trials, especially in patients with hematological malignancies. Nutlin-3a is one of the first MDM2 inhibitors isolated. Berberine (BBR) is a natural product found in many fruits and berries and used in traditional medicine for centuries. It has many biological effects, and some are anti-proliferative in nature. BBR may activate the expression of TP53 and inhibit cell cycle progression as well as other events important in cell growth. To understand more about the potential of compounds like BBR and chemical modified BBRs (NAX compounds) to sensitize PDAC cells to MDM2 inhibitors, we introduced either WT-TP53 or the pLXSN empty vector control into two PDAC cell lines, one lacking expression of TP53 (PANC-28) and one with gain-of-function mutant TP53 on both alleles (MIA-PaCa-2). Our results indicate that nutlin-3a was able to increase the sensitivity to BBR and certain NAX compounds. The effects of nutlin-3a were usually more substantial in those cells containing an introduced WT TP53 gene. These results highlight the importance of knowledge of the type of TP53 mutation that is present in cancer patients before the administration of drugs which function by stabilization of the TP53 protein.